Analysis Of Implementation Of Gakida Gold System In Unit Pegadaian Syariah (UPS) Ayahanda Medan - Arsad Halomoan Sipahutar; Murni Murni (Proceeding International Seminar of Islamic Studies, 2019)
Islamic pawnshops are one of the financial institutions that apply the concept of sharia which is far from usury (interest). The purposes of this research are: 1) To find out the implementation of the gold pawn system in the Unit Pegadaian Syariah (UPS) Ayahanda Medan. 2) to find out whether the implementation of the re-pawning system or the addition of loans at the Unit Pegadaian Syariah (UPS) Ayahanda Medan is in accordance with the DSN-MUI fatwa or not. As for the implementation of this research using qualitative methods, namely data collection that is specific in nature where the data collection is in accordance with the problems observed. After the data was obtained in the field through interviews, it was collected and then analyzed using a qualitative descriptive method, then the discussion was concluded deductively. The results of the study found that the Unit Pegadaian Syariah (UPS) Ayahanda Medan in its gold pawn transactions used two transactions, namely the rahn contract and the ijarah contract whose contract was stated in the basis of the MUI fatwa. And the result of the re-implementation of additional pawns/loans from these transactions is also in accordance with the sharia concept where as long as there is no argument against it, multi-contract transactions are allowed, according to what was said by a member of the MUI, namely Mrs. Wulan Dayu, S.E., M.E. and Ibn Taimiyah said that muamalat law in the world is basically permissible, except for what is prohibited by Allah and His Messenger. However, from the results of this research interview, there are still customers who do not understand the application of the gold pawn system to this father's sharia pawnshop unit.